Kodrat Perempuan dan Kesetaraan Gender Dalam Konsep Islam - J, Jumadiah; S, Sutriani; H, Hamdani (Socius: Jurnal Penelitian Ilmu-Ilmu Sosial, 2024)
This research discusses the nature of women from an Islamic perspective. To build equal gender relations, we need to do these things to eliminate the perception of great injustice between men and women in all aspects of life without ignoring the nature of women. Gender is not sex, but is the placement of things in human life that must be in their place and gaps must be completely eliminated so that women can achieve standing on an equal footing with men so that there is no priority over others based on gender discrimination.